Perancangan Sistem Pengarsipan Surat dan Penugasan Berbasis Web Menggunakan Framework Laravel - Yuven Prisma Dyarenggasto; Nina Setiyawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2024)
The Indonesian Red Cross, hereinafter abbreviated as PMI, is a national association organization in Indonesia that is active in the social and humanitarian fields. The letter filing system used is still done manually by recording it in a book, while the assignment system itself has been done online via the Indonesian Red Cross's own website. Using the old method, it is considered less effective because it will take a lot of time and it is easy to lose data. Therefore, we need a web-based information system that is felt to make it easier for employees to do letter filing. So in this study, it was built using the Laravel framework. The Laravel framework is used because it is considered easy to understand and has features that make it easier for developers to build the application. This study aims to facilitate employees in filing letters, assignments, and reporting the completion of assignments at the Indonesian Red Cross in Salatiga City. The research results show that this application can improve employee performance.